Illocutionary acts in the Movie of the Nanny Diaries; Pragmatics Study - Nurfithri (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
Speech act is the utterance which speaker says or speaker performs in very speech. This study investigates Speech Acts in The Nanny diaries movie cscript. The objectives of the study are to know the illocutionary act based on Searle category that is used by the main characters which is found in “The Nanny diaries” movie script and to find out the strategies that is used to reliaze the illocutionary acts by the main characters in “The Nanny diaries” movie script. There are four types of illocutionary acts based on Seale category, they are: representative, directive, commissive, and expressive. There are two types of the strategy of speech acts, there are direct and indirect speech acts. The data source of this study was the utterances from the main characters in movie from the begining until the end and it becomes data analysis.